Popillia japonica – Italian outbreak management - Gotta, Paola; Ciampitti, Mariangela; Cavagna, Beniamino; Bosio, Giovanni; Gilioli, Gianni; Alma, Alberto; Battisti, Andrea; Mori, Nicola; Mazza, Giuseppe; Torrini, Giulia; Paoli, Francesco; Santoiemma, Giacomo; et al. (Frontiers in Insect Science, 2023)
Popillia japonica, a priority pest for the EU, was first detected in Northern Italy in 2014. Since its discovery, the outbreak extended over an area of more than 16,000 square kilometers in Northern Italy and Southern Switzerland. In this review, we summarize the state-of-the-art of research conducted in Italy on both the spreading capacity and control measures of P. japonica. Chemical, physical, and biological control measures deployed since its detection are presented, by highlighting their strengths and weaknesses. An in-depth study of the ecosystems invaded by P. japonica disclosed the presence and pathogenicity of natural strains of entomopathogenic fungi and nematodes, some of which have shown to be particularly aggressive towards the larvae of this pest under laboratory conditions. The Plant Health authorities of the Lombardy and Piedmont regions, with the support of several research institutions, played a crucial role in the initial eradication attempt and subsequently in containing the spread of P. japonica. Control measures were performed in the infested area to suppress adult populations of P. japonica by installing several traps (e.g., for mass trapping, for auto-dissemination of the fungus Metarhizium anisopliae, and “attract & kill”). For larval control, the infested fields were treated with commercial strains of the entomopathogenic fungus M. anisopliae and nematode Heterorhabditis bacteriophora. Future studies will aim at integrating phenological and spread models developed with the most effective control measures, within an ecologically sustainable approach.